ANALYSIS OF ADM (ALTERNATIVE LEARNING MODALITIES) TRYOUTS: BASIS FOR MONITORING AND EVALUATION OF DISTANCE EDUCATION IMPLEMENTATION (World Bulletin of Social Sciences, 2021)
The upsurge of global pandemic has turned events into 360 degrees. Things have drastically changed from what they termed normal to new appealing phrase ‘new normal’. COVID-19 has dramatically changed the lives of people across the globe and distance education has become the norm. The study utilized explanatory sequential mixed design in assessing the alternative learning modalities tryouts as a basis for monitoring and evaluation of distance education implementation in the City Schools Division of San Jose del Monte. The findings of the study revealed that there were different distance learning modalities utilized where 1, 758 modules were successfully distributed, and 1, 756 or 99.9% were retrieved. Also, 181 learners registered for online distance learning platform and 100% of them successfully finished the sessions. Further, there were 456 learners who successfully engaged in the conducted 2-week simulation using blended modular and online learning simulation. Qualitative data showed that schools encountered common problems during the tryouts. School heads reported that there were problems with the learners’ internet connectivity, distribution and retrieval of the modules, availability of assigned vehicle, tardiness, lack of tech-skills, locating the house of the learners, and insufficient access to a working microphone and camera, rendering them unable to participate during recitation. The researchers concluded that the key players of distance education are stakeholders and resources, and there is a dire need to consider how the relationship of these key players are constructed depending on the modality employed and technologies available in the geographical area. The support of internal and external stakeholders of the school has a central role impacting the effectiveness of distance education implementation